Adobe Photoshop Elements 10 maximum performance : unleash the hidden performance of Elements - Galer, Mark (Focal, 2012)
Master the most powerful photo editing tools and techniques that Elements has to offer! Using step-by-step projects, Mark Galer will have you creating stunning images in no time at all. Whether you want to create impressive, seamless montages, optimize your photos for perfect print quality, or simply enhance your images for maximum impact, Maximum Performance will give you the skills and know-how you need to create professional quality results. Featured projects teach you how to work with multilayered 16 bit/channel files, as well as convert to black and white using Adobe Camera Raw, create High Key images, work with image borders and textures, and create tilt-shift and cross-process effects. Find everything you need to unleash the power of Elements with Max Performance, or for a more interactive learning experience, download the supplemental images and movies for comprehensive, hands-on learning. Get professional, Photoshop-quality results with affordable, Elements-priced software Create amazing images using advanced, little-known techniques to achieve results you never thought possible Learn and master advanced techniques using step-by-step, project-based tutorials that are intuitive and easy to follow.
Keywords: Adobe Photoshop elements; Photography -- Digital techniques; Photographie numérique; Photography; Digital techniques